2008
DOI: 10.2147/copd.s2103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of add-on therapy of tiotropium in COPD treated with theophylline

Abstract: Background: Although combination therapy with bronchodilators is recommended for chronic obstructive pulmonary disease (COPD), there is insuffi cient evidence for the effi cacy of some combinations of long-acting bronchodilators. Objective: We investigated the effects of a combination therapy with tiotropium and theophylline in COPD patients. Methods: In a 12-week, open-labeled, parallel-group randomized study, pulmonary functions and dyspnea scores were compared between the combination and theophylline alone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…Safety outcomes were reported in 17 studies . 27,29,36,38,[40][41][42][43]45,[47][48][49]51,52,[55][56][57] The adverse effects observed were consistent with those reported with theophylline. This included gastrointestinal (nausea, diarrhea, vomiting, heartburn, appetite suppression) and neurologic (headache, insomnia, dizziness, tremors) adverse effects.…”
Section: Safetysupporting
confidence: 85%
See 3 more Smart Citations
“…Safety outcomes were reported in 17 studies . 27,29,36,38,[40][41][42][43]45,[47][48][49]51,52,[55][56][57] The adverse effects observed were consistent with those reported with theophylline. This included gastrointestinal (nausea, diarrhea, vomiting, heartburn, appetite suppression) and neurologic (headache, insomnia, dizziness, tremors) adverse effects.…”
Section: Safetysupporting
confidence: 85%
“…51 In one outpatient study in Japan, the addition of tiotropium to theophylline improved dyspnea and pulmonary function in patients with COPD. 49 The addition of theophylline to salmeterol treatment offered no advantage over salmeterol alone in outpatients with well-controlled COPD. 39 One study of outpatients in Italy found that adding oral theophylline to a combination of formoterol and tiotropium did not provide significant further improvement in lung function and dyspnea in patients with stable COPD.…”
Section: Inflammation Spirometry and Symptomsmentioning
confidence: 99%
See 2 more Smart Citations
“…Theophylline, also known as 1,3-dimethylxanthine, is a proven bronchodilator drug used in therapy for respiratory diseases such as asthma or chronic pulmonary obstructive disease (COPD) (Black et al 1990;Cazzola and Gabriella 2007;Majumdar and Sloan 2007a, b;Kawayama et al 2008;Korzycka and Górska 2008).…”
Section: Introductionmentioning
confidence: 99%